2017
DOI: 10.3892/mmr.2017.6578
|View full text |Cite
|
Sign up to set email alerts
|

PER2 is downregulated by the LPS-induced inflammatory response in synoviocytes in rheumatoid arthritis and is implicated in disease susceptibility

Abstract: The clinical symptoms of rheumatoid arthritis (RA) present with circadian variation, with joint stiffness and pain more prominent in the early morning. The mammalian clock genes, which include circadian locomotor output cycles kaput, brain and muscle Arnt-like protein 1, period and cryptochrome, regulate circadian rhythms. In order to identify the association between genetic polymorphisms in the circadian clock gene period 2 (PER2) and RA, the present study genotyped three PER2 single nucleotide polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Previous research has demonstrated that Per2 expression was reduced in non-tumourigenic breast epithelial cells stimulated by IL-6 [33]. Further, immunoblotting analysis showed the Per2 protein expression was inhibited in LPS-treated rheumatoid arthritis synovial cells [34]. In the present study, Per2 mRNA expression was markedly lower in NHAC-kn cells treated by LPS than normal NHAC-kn cells.…”
Section: Discussionsupporting
confidence: 55%
“…Previous research has demonstrated that Per2 expression was reduced in non-tumourigenic breast epithelial cells stimulated by IL-6 [33]. Further, immunoblotting analysis showed the Per2 protein expression was inhibited in LPS-treated rheumatoid arthritis synovial cells [34]. In the present study, Per2 mRNA expression was markedly lower in NHAC-kn cells treated by LPS than normal NHAC-kn cells.…”
Section: Discussionsupporting
confidence: 55%
“…LPS is a potent endotoxin involved in the progression of RA diseases (36). LPS treatment (100 ng/ml) for 12 h markedly increased the mRNA and protein expression levels of TNF-α, IL-1β, IL-6 and IL-8 in the PBMCs of patients with RA by between 3- and 10-fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This causes tissue destruction via MAC (Cao et al, 2017 ) and exacerbating effector cell inflammation (Perez-Aso et al, 2013 ; Sadik et al, 2018 ). Although anti-inflammatory components, such as HO-1 are also induced in the synovial joints, the levels of HO-1 are shown to decline with the advanced immunopathogenesis of RA (Kitamura et al, 2011 ; May et al, 2018 ), which is presumably moderated by the RA-driven proinflammatory circadian responses (Lee et al, 2017 ). Thus, the second regulatory loop of the core transcriptional circadian clock proteins also plays an important role in immune response and complement signaling ( Figure 2 -top blue panel 2; bottom orange panel).…”
Section: Complement and Circadian Signalingmentioning
confidence: 99%